Protective value of immune responses developed in goats vaccinated with insoluble proteins from Sarcoptes Scabiei - Simson Tarigan (Indonesian Center for Animal Research and Development (ICARD), 2005)
Vaccines developed from certain membrane proteins lining the lumen of arthropod’s gut have been demonstrated effective in the control of some arthropod ectoparasites. A similar approach could also be applied to Sarcoptes scabiei since this parasite also ingests its host immunoglobulins. To evaluate immune protection of the membrane proteins, insoluble mite proteins were fractionated by successive treatment in the solutions of 1.14 M NaCl, 2% SB 3-14 Zwitterion detergent, 6 M urea, 6 M guanidine-HCl and 5% SDS. Five groups of goats (6 or 7 goats per group) were immunised respectively with the protein fractions. Vaccination was performed 6 times, each with a dosage of 250 μg proteins, and 3 week intervals between vaccination. Group 6 (7 goats) received PBS and adjuvant only, and served as an unvaccinated control. One week after the last vaccination, all goats were challenged with 2000 live mites on the auricles. The development of lesions were examined at 1 day, 2 days, and then every week from week 1 to 8. All animals were bled and weighed every week, and at the end of the experiment, skin scrapings were collected to determine the mite burden. Antibody responses induced by vaccination and challenge were examined by ELISA and Western blotting. This experiment showed that vaccination with the insoluble-protein fractions resulted in the development of high level of specific antibodies but the responses did not have any protective value. The severity of lesions and mite burden in the vaccinated animals were not different from those in the unvaccinated control. Key Words: Sarcoptes scabiei, Insoluble Protein, Goat, Vaccination